2014
DOI: 10.1007/s11224-014-0515-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic investigations of hydrogen storage efficiency of graphene sheets with the bubble structure

Abstract: In this paper, we designed a new type of 3D graphene bubble structure for hydrogen storage in theory. The graphene-based structures are constructed with different sizes of semi-ellipsoidal graphene bubbles. The hydrogen storage efficiency of the graphene bubble structures at ambient conditions (P = 1.0 bar and T = 300 K) is calculated using molecular dynamic (MD) simulations. The effects of number of graphene layers and density and size of bubbles are systematically investigated in the isothermal-isobaric (NPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Most previous theoretical studies have been focused on the height-to-radius ratio. ,,, However, if one hopes to solve the individual structural parameters ( h , a ) for the graphene bubble, the gas state equation is needed to provide the second equation for these two geometrical parameters. We first consider the ideal gas law, italicp italicV = N k normalB T where N is the gas molecule number.…”
Section: Resultsmentioning
confidence: 99%
“…Most previous theoretical studies have been focused on the height-to-radius ratio. ,,, However, if one hopes to solve the individual structural parameters ( h , a ) for the graphene bubble, the gas state equation is needed to provide the second equation for these two geometrical parameters. We first consider the ideal gas law, italicp italicV = N k normalB T where N is the gas molecule number.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous works have primarily concentrated on the ratio of bubble height to radius. [42][43][44][45] To gain further insights into the relationship between bubble shape and their applications, it is important to derive specific expressions for each structural parameter, including bubble height and radius.…”
Section: Bubble Structurementioning
confidence: 99%
“…Jiang et al [127] suggested a novel graphene bubble structure and used molecular dynamics (MD) to investigate its hydrogen storage efficiency at a pressure of 1.0 bar and a temperature of 300 K. The calculated maximum gravimetric and volumetric H 2 densities of the graphene bubble models were 3.75 % ( m / m ) and 0.045 g cm -3 , respectively. 1,3-and 1,4-cyclohexadiene are two partially hydrogenated benzenes with nearly the same enthalpy of formation [128].…”
Section: Issuementioning
confidence: 99%